A Bibliometric Analysis: The Dynamics of Zakat and Poverty Research - Dupi, Muhamad (UIN Sunan Kudus, 2025)
This study performs an exhaustive bibliometric analysis to delineate the global dynamics, thematic progression, and intellectual framework of zakat and poverty research from 2009 to 2025, utilizing Scopus-indexed publications. Following PRISMA-guided screening procedures, 290 English-language journal articles were chosen. We used bibliometric methods, with the help of VOSviewer and Microsoft Excel, to look at publication trends, important authors, popular journals, networks of collaboration between countries and institutions, and patterns of keyword co-occurrence. The results show that the number of publications is growing quickly and significantly, with Malaysia and Indonesia being the primary contributors to the field. Institutional networks reveal robust academic clusters in Southeast Asia, whereas journal coupling points to the importance of publications like the Journal of Islamic Accounting and Business Research and the International Journal of Islamic and Middle Eastern Finance and Management. Keyword mapping shows six main thematic clusters: poverty alleviation, zakat governance, Islamic microfinance, financial inclusion, digital innovation, and sustainable development. Overlay visualization shows that the topics have changed from traditional ones like charity, welfare, and poverty to more modern ones like fintech, blockchain, productive zakat, and the SDGs. Even though the field is growing quickly, there are still gaps in high-impact scholarship, governance frameworks, and global collaboration.